Microwave Ablation of Primary Malignant Pelvic Bone Tumors - Fan, Qing-Yu; Zhou, Yong; Zhang, Minghua; Ma, Baoan; Yang, Tongtao; Long, Hua; Yu, Zhe; Li, Zhao (Frontiers in Surgery, 2019)
Background: En bloc tumor resection followed by reconstruction is a widely used surgical treatment for malignant pelvic bone tumors. High rates of complications and mechanical instability often contribute to poor postoperative results. We attempted en bloc microwave ablation (MWA) in situ to improve the outcome. Methods: From May 1995 to December 2015, 104 patients with primary pelvic malignancy received radical MWA in our department. After careful dissection of the tumor-bearing bone from surrounding normal tissues with safe margins, a microwave antenna array was inserted into the tumor mass to emit electromagnetic energy, inducing tumor cellular death via thermocoagulation. The loose, devitalized tumor tissues were removed by cutting or curettage, leaving a defective bone scaffold. Restrengthening by autograft or allograft was needed in most patients. Results: The over 3-year survival rate was 51.5% for high-grade malignancies (among them, 26.9% were osteosarcoma) and 94.8% for low-grade malignancies (chondrosarcoma). In most of the living patients, cosmetic and useful limbs were preserved. The mean functional score (Musculoskeletal Tumor Society) was 27, or 90% (range: 25-30, 75-100%). Among the 56 patients who belonged to the excellent function group, 11 were followed up for more than 10 years. The local recurrence rate was 8.6%. Among the 9 patients with recurrence, 5 died from disease, 2 were treated by hemipelvic amputation, and 2 underwent revision surgery with MWA and gained local control. The deep infection rate was 5.6%. All six patients with infection were healed by irrigation, debridement, and systemic antibiotic administration. Conclusion: Local, microwave-induced hyperthermia for treating malignant pelvic bone tumors is an effective alternative method. The oncological and functional results are encouraging. The use of MWA should be continued to evaluate and improve this new therapeutic system.